2020
DOI: 10.1111/ijlh.13228
|View full text |Cite
|
Sign up to set email alerts
|

Identification of acquiredPIGAmutations and additional variants by next‐generation sequencing in paroxysmal nocturnal hemoglobinuria

Abstract: IntroductionParoxysmal Nocturnal Hemoglobinuria (PNH) is an acquired clonal disease of hematopoietic stem cells. It is caused by somatic mutation of the X‐linked PIGA gene, resulting in a deficient expression of glycosylphosphatidylinositol‐anchored proteins (GPI‐APs). In this study, we aimed to explore the diagnostic value of next‐generation sequencing (NGS) and potential molecular basis in PNH patients.MethodsGenomic DNA of 85 PNH patients was analyzed by a 114‐gene NGS panel.ResultsMutational analysis of PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…Furthermore, two subsets of mutations were associated with early infantile epileptic-dyskinetic encephalopathy; first is the homozygous c.384del variant of PIG-P gene (25), which led to the frame shift of 6 codons before the expected stop signal (25), and second are PIG-Q mutations, particularly PIG-Q novel variants, which included two missense mutations (p.G17R; p.G449R), a canonical splice site substitution (c.942+1G>A), an in-frame deletion (p.A377_S389del) and three frameshifts (p.Q527Afs*75, p.R538Afs*24 and p.G557Dfs*) (26). Finally, mutational analysis of PIGA identified 124 PIG-A mutations in 92% of paroxymal nocturnal hemoglobinuria (PNH) patients, of which 101 were distinct mutations and 23 were recurrent (27).…”
Section: Gpi Mutations In Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, two subsets of mutations were associated with early infantile epileptic-dyskinetic encephalopathy; first is the homozygous c.384del variant of PIG-P gene (25), which led to the frame shift of 6 codons before the expected stop signal (25), and second are PIG-Q mutations, particularly PIG-Q novel variants, which included two missense mutations (p.G17R; p.G449R), a canonical splice site substitution (c.942+1G>A), an in-frame deletion (p.A377_S389del) and three frameshifts (p.Q527Afs*75, p.R538Afs*24 and p.G557Dfs*) (26). Finally, mutational analysis of PIGA identified 124 PIG-A mutations in 92% of paroxymal nocturnal hemoglobinuria (PNH) patients, of which 101 were distinct mutations and 23 were recurrent (27).…”
Section: Gpi Mutations In Diseasesmentioning
confidence: 99%
“…Some studies tested the impact of GPI pathway manipulation on dependent GPI-anchored complement regulatory protein, CD-59, which was found to be under expressed in congenital and neurological disorders, as well as PNH (21)(22)(23)(24)(25)(26)(27). CD-59 was, however, overexpressed in most solid tumors (28).…”
Section: Gpi Mutations In Diseasesmentioning
confidence: 99%
“…Directly relating to brain MVs, GPI-APs have been reported to regulate leukocyte adhesion and thereby protect endothelium from damage. 23 Defects in the GPI-anchor synthesis occur in paroxysmal nocturnal hemohemoglobinuria 24 and congenital diseases. 25 Reck, a GPI-AP, plays an important role in neurovascular development.…”
Section: Glycosylphosphatidylinositol (Gpi Male Enhancement)mentioning
confidence: 99%
“…Directly relating to brain MVs, GPI-APs have been reported to regulate leukocyte adhesion and thereby protect endothelium from damage. 23 Defects in the GPI-anchor synthesis occur in paroxysmal nocturnal hemohemoglobinuria 24 and congenital diseases. 25 Reck, a GPI-AP, plays an The results for statistical significance of (e) using merged western blot data were identical whether we used the Student's t-test or two-way analysis of variance.…”
Section: Glycosylphosphatidylinositol (Gpi Male Enhancement)mentioning
confidence: 99%
“…Furthermore, the application of NGS in PNH patients demonstrated that the mutations of myeloid neoplasm-related genes (i.e., TET2 , SUZ12 , U2AF1 , JAK2 , ASXL1 , DNMT3A , etc.) could be acquired in addition to the PIGA gene mutation [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%